Dual Regulation of Bacillus subtilis kinB Gene Encoding a Sporulation Trigger by SinR through Transcription Repression and Positive Stringent Transcription Control - Fujita, Yasutaro; Ogura, Mitsuo; Nii, Satomi; Hirooka, Kazutake (Frontiers in Microbiology, 2017)
It is known that transcription of kinB encoding a trigger for Bacillus subtilis sporulation is under repression by SinR, a master repressor of biofilm formation, and under positive stringent transcription control depending on the adenine species at the transcription initiation nucleotide (nt). Deletion and base substitution analyses of the kinB promoter (PkinB) region using lacZ fusions indicated that either a 5-nt deletion (delta5, nt -61/-57, +1 is the transcription initiation nt) or the substitution of G at nt -45 with A (G-45A) relieved kinB repression. Thus, we found a pair of SinR-binding consensus sequences (GTTCTYT; Y is T or C) in an inverted orientation (SinR-1) between nt -57/-42, which is most likely a SinR-binding site for kinB repression. This relief from SinR repression likely requires SinI, an antagonist of SinR. Surprisingly, we found that SinR is essential for positive stringent transcription control of PkinB. Electrophoretic mobility shift assay (EMSA) analysis indicated that SinR bound not only to SinR-1 but also to SinR-2 (nt -29/-8) consisting of another pair of SinR consensus sequences in a tandem repeat arrangement; the two sequences partially overlap the ‘-35’ and ‘-10’ regions of PkinB. Introduction of base substitutions (T-27C C-26T) in the upstream consensus sequence of SinR-2 affected positive stringent transcription control of PkinB, suggesting that SinR binding to SinR-2 likely causes this positive control. EMSA also implied that RNA polymerase and SinR are possibly bound together to SinR-2 to form a transcription initiation complex for kinB transcription. Thus, it was suggested in this work that derepression of kinB from SinR repression by SinI induced by Spo0A~P and occurrence of SinR-dependent positive stringent transcription control of kinB might induce effective sporulation cooperatively, implying an intimate interplay by stringent response, sporulation, and biofilm formation.